PENERAPAN KURIKULUM BERDIFERENSIASI DALAM SETTING SEKOLAH INKLUSIF (Studi Kasus Di SDN Junrejo 1, SDN Beji 1, SD Lazuardi Kamila GIS dan SDN Bromantakan ) - Dwi Arnia Ulfa; Sunardi Sunardi; Abdul Salim (FKIP Universitas Samawa, 2022)
This study aims to describe the implementation of differentiated curriculum in 4 inclusive schools. The method used in this research is qualitative research type case study.Technique of collecting data in this research is interview. Data analysis are done through data reduction, data presentation and conclusion. The research was conducted at SDN Junrejo 1, SDN Beji 1, SD Lazuardi Kamila and SDN Bromantakan. Based on the results of the research, it was found that (1) the 4 inclusive schools have undertaken a differentiated curriculum in the setting of inclusive schools due to modifications in intended goals, content, process and evaluation components, (2) there is a collaborative team in the implementation of differentiated curriculum, but there should be awareness raising of all school personnel related to the implementation of the differentiated curriculum in the setting of inclusive schools, and (3) the evaluation of the differentiated curriculum has been carried out although there are still those who have not conducted regular evaluations regarding the implementation of the differentiated curriculum.